Fiscal policy under low interest rates - Blanchard, Olivier (Olivier J.) (Cambridge, Massachusetts The MIT Press, 2023)
A guide for fiscal policymakers in advanced economies to understand the appropriate policy response to an environment of high national debt and low interest rates"--
PART 1 - Introduction - -PART 2 - Preliminaries - - The Neutral Interest Rate, r* - - Safe Rates and Risky Rates, r and r+x - - The Role of Central Banks: Trying to Achieve r = r* - - Why Is "r<g" So Important? - - Nominal and Real Rates and the ELB - - Conclusions - -PART 3 - The Evolution of Interest Rates, Past and Future - - The Evolution of the Safe Rate - - Interest Rates and Growth Rates - - The Role of Demographics - - Conclusions - -PART 4 - Debt Sustainability - - The Surprising Debt Dynamics When (r-g) <0 - - Uncertainty, Sustainability, and Fiscal Space - - Can One Design Good Sustainability Rules? - - Public Investment and Debt Sustainability - - Multiple Equilibria and the Role of Central Banks - - Central Banks, Bailouts, and Write-Offs - - Conclusions - -PART 5 - Welfare Costs and Benefits of Debt and Deficits - - Debt and Welfare under Certainty - - Debt and Welfare under Uncertainty - - Fiscal Policy, the ELB, and Output Stabilization - - Putting the Threads Together - -PART 6 - Fiscal Policy in Action - - Fiscal Austerity in the Wake of the GFC - - The Japanese Experience: Success or Failure? - - The Biden Bet: r, r*, and g - -PART 7 - Summary and Open Issues - - Bibliography - - Index.
Includes bibliographical references and index.
Keywords: Debts, Public; Fiscal policy; Interest rates; Social policy